Co-design methodology for rapid prototyping of modular robots in care settings - Alexandre Colle; Alexandre Colle; Alexandre Colle; Alexandre Colle; Alexandre Colle; Karen Donaldson; Karen Donaldson; Mauro Dragone; Mauro Dragone; Mauro Dragone (Frontiers in Robotics and AI)
IntroductionThis paper introduces a structured co-design methodology for developing modular robotic solutions for the care sector. Despite the widespread adoption of co-design in robotics, existing frameworks often lack clear and systematic processes to effectively incorporate user requirements into tangible robotic designs.MethodTo address this gap, the present work proposes an iterative, modular co-design methodology that captures, organises, and translates user insights into practical robotic modules. The methodology employs Design Research (DR) methods combined with Design for Additive Manufacturing (DfAM) principles, enabling rapid prototyping and iterative refinement based on continuous user feedback. The proposed approach was applied in the development of Robobrico, a modular robot created collaboratively with care home users.ResultsOutcomes from this study demonstrate that this structured process effectively aligns robot functionality with user expectations, enhances adaptability, and facilitates practical integration of modular robotic platforms in real-world care environments.DiscussionThis paper details the proposed methodology, the tools developed to support it, and key insights derived from its implementation.